Working with Mistakes in Psychotherapy - A Relational Model - Žvelc, Maša (European Journal for Qualitative Research in Psychotherapy, 2008)
In the article I deal with the question what is the meaning of mistakes, done by therapist in psychotherapy and how to work with mistakes. With the word mistakes I think of moment-to- moment mistakes, often very small and subtle, made by the therapist, which can lead to ruptures in the therapeutic relationship. I see repairing ruptures of the relationship as a very important way of establishing or solidifying good therapeutic alliance. In the article I present relational methods of integrative psychotherapy- inquiry, attunement and involvement (Erskine, Trautmann & Moursund, 1999) and Safran and Muran’s (2000) model of negotiating therapeutic alliance, which both lead us how to work with the mistakes. In the second part of the article I analyze one session with the client in which I explore the practical use of the model for working with mistakes.